Preface [proceedings of the European Optical Society Annual Meeting, EOSAM2022] - Costa, Manuel F. M. (2022)
The European Optical Society Annual Meeting, EOSAM, is a major international scientific conference covering all aspects of optics and photonics, covered by the topical meetings and sessions. EOSAM was celebrated this year in Portugal, at the Faculty of Engineering of the University of Porto, FEUP, in co-operation with the Portuguese Society for Research and Development in Optics and Photonics, SPOF, and INESC TEC - Institute for Systems and Computer Engineering, Technology and Science.